Factor affecting Implementation Diversion To Child Perpetrator Action Criminal Distribution of Pornographic Videos in the Gorontalo Regional Police - Mokodongan, Indryati; Puluhulawa, Fenty U.; Mamu, Karlin Z. (Universitas Negeri Gorontalo, 2025)
This research aims For discussing the application of diversion for children who are perpetrators of the crime of distributing pornographic videos from the perspective of legal protection against children's rights as victims and causal factors . The method used in the research is legal empirical with qualitative descriptive data analysis that describes and explains data and field facts. The results of the study show that the application of diversion to children who are perpetrators of the crime of distributing pornographic videos, viewed from the legal protection of children as victims in Gorontalo, is basically to protect children as perpetrators of crimes and provide them with the opportunity to improve themselves and not affect their future. This is also one of the legal policies in the context of protecting children as perpetrators of pornography crimes. However, the implementation of diversion still has an impact on the existence of mental/psychological and physical pressure on children as victims. Therefore, from the aspect of protection for victims, the implementation of diversion in cases of the distribution of pornographic videos does not pay enough attention to the rights and mentality of the victim, because the perpetrator continues to distribute the video to his friends during the mediation process. However, the PPA unit of the Gorontalo Regional Police prioritizes the resolution of children's cases outside the court through this diversion and is the main choice in its resolution, on the grounds that there is no deviation from the requirements of diversion, namely criminal acts with a threat of less than 7 years and not a repetition of the crime. The factors that influence the implementation of diversion against children who are perpetrators of the crime of distributing pornographic videos at the Gorontalo Regional Police are the Intention of the Perpetrator and Family and economic capacity limitations; Lack of public understanding; and The absence of LPSK in Gorontalo thus hindering and influencing the provision of decisions on compensation that must be received by families and victims of the distribution of pornographic content in Gorontalo.